(untitled) (مجلة إحالات, 2025)
يروم هذا البحث دراسة العنف باعتباره ظاهرة اجتماعية ارتبطت بالإنسانية منذ القدم، ويسعى للإجابة عن مجموعة من الفرضيات التي تبحث عن أصول العنف ومنشئه، معتمدة على المقاربة الدينية التاريخية للعنف عند الفيلسوف طه عبد الرحمن، والمقاربة التجريبية للعنف عند إريك فروم. فهل يمكن اعتبار العنف حادث طارئ على الإنسانية، أم أنه يشكل سمة مميزة للإنسان؟ وما علاقة العنف بالطبيعة البشرية الإنسانية؟ وكيف يقع العنف سيكولوجيا؟ This research aims to study the violence as a social phenomenon that has been associated withhumanity since ancient times, and seeks to answer a set of hypotheses that search for the origins of violence relying on the historical and religious approach to violence by the philosopher Taha Abdel Rahman, and the empirical approach to violence by Erich Fromm. This rises the question as to whether violence can be considered a new event for humanity, or is it a distinctive feature of the human? What is the relationship between violence and the human Manly nature? And how does violence act psychologically speaking?